Return Migration and Identity Conflicts - Piñeiro Domínguez, María Jesús (Madrygal. Revista de Estudios Gallegos, 2020)
The emigration of the Galician population during the postwar period was very high, as well as the number of migrants that came back, especially during the transition. For them, it was difficult leaving the country and also returning to a place in apparent democracy, but still in conflict because of the unrestored wounds of the war. The analysis of several essays and novels focused on the return will allow us to reflect on the consequences of coming back to the origins and its impact on family, social and political areas, among others. We talk about identity break-up, chronic maladjustment, generational clash, disappointment, or uprooting, as an example of situations that evidence how identity is in conflict and in permanent (de)construction.